Aislamiento e identificación de rotavirus de terneros neonatos. - Mogollón Galvis, José Darío; Rodríguez T, Gerzaín.; Cortés Castillo, Esperanza; Hernández de Galvis, Alba Lucia (Instituto Colombiano Agropecuario - ICA, 2018)
Ganadería bovina